2017
DOI: 10.15761/iod.1000176
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high-dose teneligliptin, a dipeptidyl peptidase-4 inhibitor, for glycemic parameters in patients with type 2 diabetes estimated with continuous glucose monitoring: A pilot study

Abstract: Background: Few studies have focused on the "glucose-normalizing effects" of high and standard doses of dipeptidyl peptidase-4 (DPP-4) inhibitors evaluated using continuous glucose monitoring (CGM). Teneligliptin is a DPP-4 inhibitor licensed in Japan for administration at standard (20 mg/day) and high (40 mg/day) doses to treat type 2 diabetes mellitus. However, little is known about its effects on the "quality" of glucose control or plasma glucose fluctuation, including factors such as postprandial glucose l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Postprandial glucose excursions, 24-h mean glucose values, and fasting plasma glucose levels were all significantly reduced with teneligliptin compared with placebo. A recent pilot study using continuous glucose monitoring to compare the effects of teneligliptin 20 and 40 mg doses in hospitalized patients with type 2 diabetes observed a significant dose-dependent reduction in the mean amplitude of glycemic excursions and maximum glucose levels [ 23 ]. High-dose teneligliptin also significantly increased minimum glucose concentrations compared with the standard dose, suggesting that teneligliptin 40 mg may provide better “quality” glucose control by reducing the risk of hypoglycemia, and may suppress diabetic complications arising from micro- and macroangiopathies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postprandial glucose excursions, 24-h mean glucose values, and fasting plasma glucose levels were all significantly reduced with teneligliptin compared with placebo. A recent pilot study using continuous glucose monitoring to compare the effects of teneligliptin 20 and 40 mg doses in hospitalized patients with type 2 diabetes observed a significant dose-dependent reduction in the mean amplitude of glycemic excursions and maximum glucose levels [ 23 ]. High-dose teneligliptin also significantly increased minimum glucose concentrations compared with the standard dose, suggesting that teneligliptin 40 mg may provide better “quality” glucose control by reducing the risk of hypoglycemia, and may suppress diabetic complications arising from micro- and macroangiopathies [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our previous study observed similar efficacy with 10, 20, and 40 mg doses [ 21 ], a dose-dependent reduction in HbA1c was observed over 24 weeks with teneligliptin 5–40 mg added to metformin therapy [ 22 ]. More recently, teneligliptin 40 mg was shown to reduce the mean amplitude of glycemic excursions and to increase minimum glucose concentrations compared with teneligliptin 20 mg in hospitalized patients with type 2 diabetes, suggesting that the higher dose may provide better “quality” glucose control by reducing the risk of a hypoglycemia event [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with effects of standard-dose Teneligliptin, MAGE, SD, and maximum glucose concentrations were significantly reduced by high-dose Teneligliptin (p < 0.01) but there was no significant difference in mean glucose concentrations (p = 0.0314). 5 • Mean postprandial blood glucose when Teneligliptin 20 mg was increased to 40 mg was 201.5 ± 65.5 mg/dL. • Mean HbA1C when Teneligliptin 20 mg was increased to 40 mg was 8.1 ± 1.5%.…”
Section: Methodsmentioning
confidence: 98%
“…A previous study showed a statistically non-significant difference in results on HbA1c levels mediated by the standard dose (−0.9% vs. placebo) and a high dose of teneligliptin (−1.0% vs. placebo) [16]. A high dose of teneligliptin exerts proper glycemic control in DM patients [17]; it also takes part in the improvement of insulin resistance [18][19].…”
Section: Introductionmentioning
confidence: 98%